Prevalence and correlates of regional pain and associated disability in Japanese workers. Issue 3 (10th September 2010) - Matsudaira, Ko; Palmer, Keith T; Reading, Isabel; Hirai, Masami; Yoshimura, Noriko; Coggon, David
Abstract : Objectives: To assess the prevalence and correlates of regional pain and associated disability in four groups of Japanese workers. Methods: As part of a large international survey of musculoskeletal symptoms (the CUPID study), nurses, office workers, sales/marketing personnel and transportation operatives in Japan completed a self-administered questionnaire (response rate 83%) covering experience of pain in six anatomical regions, associated disability and sickness absence, and various possible occupational and psychosocial risk factors for these outcomes. Associations with risk factors were assessed by logistic regression. Results: Analysis was based on 2290 subjects. Rates of regional pain were generally less than in the UK, with a particularly low prevalence of wrist/hand pain among office workers (6% in past month). The strongest and most consistent risk factor for regional pain in the past month was tendency to somatise (ORs (95% CIs) for report of ≥2 versus 0 distressing somatic symptoms 3.1 (2.4 to 4.0) for low back pain, 2.8 (2.1 to 3.8) for shoulder pain, and 2.5 (1.6 to 4.1) for wrist/hand pain). Sickness absence for regional pain complaints in the past year was reported by 5% of participants, the major risk factor for this outcome being absence during the same period for other medical reasons (OR 3.7, 95% CI 2.4 to 5.8). Conclusions: Japanese office workers have markedly lower rates of wrist/hand pain than their UK counterparts. In Japan, as in Western Europe, somatising tendency is a major risk factor for regional pain. Sickness absence attributed to regional pain complaints appears to be much less common in Japan than in the UK, and to be driven principally by a general propensity to take sickness absence.